The electricity before Faraday. Part 2 - Gabriel Poveda Ramos (Revista Facultad de Ingeniería Universidad de Antioquia, 2004)
This is the second and final part of this paper. The first part appeared in the former issue. This part deals with the period of the so-called Modern Age after the Renaissance, until the times of Faraday. Here the discoveries and inventions in the theory and practice of electricity made in that period are presented. Today they constitute a very important part of that science with the name of electrostatics. This final part reaches to Faraday because this great scientist merged in one body of knowledge two aspects: electricity and magnetism.